Metody terapeutyczne, wykorzystywane we wspomaganiu funkcjonowania poznawczego osób z udarem niedokrwiennym - Bączyk , Martyna; Jakoniuk-Diallo , Anna (Studia Edukacyjne, 2022)
An ischemic stroke is one of the most common causes of human death and disability, especially among the elderly. However, the condition affects people of all ages. The article outlines the possible consequences of an ischemic stroke depending on the affected brain area. It describes examples of therapeutic activities carried out by special educators, psychologists and speech therapists aimed at restoring at least some of the cognitive and communication skills of people affected by the disease. Of particular interest was the role of ergotherapy.